2021
DOI: 10.1111/ijcp.14089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID‐19 phobia and the feeling of loneliness in the geriatric age group

Abstract: Objective Social isolation and quarantine are unusual precautions taken all over the world against the COVID‐19 pandemic. Some legal sanctions were made in order to protect vulnerable age groups such as the geriatric population, to make them stay at home. These measures, which are vital for pandemic management, have negative psychological effects on elderly individuals. The aim of this study was to reveal how pandemic process affected individuals over 65 years old psychosocially. Materials and methods Socio‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
6
17
0
5
Order By: Relevance
“…Gender differences were found in the values of C19PRS and C19PS, with women scoring higher, which is in line with the results of Cihan and Durmaz [30], who found phobia scores significantly higher in women. Additionally, Rodriguez-Besteiro et al [48] found that females presented a higher perception of danger (assessed by the risk perception scale) related to the COVID-19 virus than males.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gender differences were found in the values of C19PRS and C19PS, with women scoring higher, which is in line with the results of Cihan and Durmaz [30], who found phobia scores significantly higher in women. Additionally, Rodriguez-Besteiro et al [48] found that females presented a higher perception of danger (assessed by the risk perception scale) related to the COVID-19 virus than males.…”
Section: Discussionsupporting
confidence: 89%
“…Toprak et al [29] found that individuals who stayed at home had higher coronaphobia than individuals who continued to work during the 3-month COVID-19 pandemic lockdown. According to Cihan and Durmaz [30], phobia scores were significantly higher in women, singles, people living alone, those living in an apartment, and those with higher economic and educational levels. Durmu and Durar [31] found a significant negative relationship between spiritual meaning and individuals' fear of coronavirus, and between peace and fear of coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…As older adults are more satisfied with their friendships and life ( 34 , 35 ), this may explain why older adults are less likely to feel lonely. We also found an inverse association between education level and loneliness, which is consistent with a recent study conducted in Turkey ( 36 ), but contrary to the findings of several previous studies ( 5 , 31 ). Considering that older and less educated individuals are more likely to be satisfied with their lives ( 35 ), increased overall life satisfaction may also be associated with a reduction in their loneliness.…”
Section: Discussionsupporting
confidence: 87%
“…También se halló una asociación entre el lugar de residencia como las zonas urbanas, y la presencia de ansiedad o pensamientos rumiantes como factores predictivos de insomnio, ya que provocan una excitación cognitiva, lo que puede alterar la homeostasis del cortisol, dando como resultado un sueño insuficiente [9] . Asimismo, se identificó que aquellos que presentaban mayor fobia hacia la COVID-19, eran precisamente mujeres, solteras, que vivían solas y tenían un nivel socioeconómico más alto [42] .…”
Section: Aislamiento Social Y Efectos Psicológicosunclassified